Development and evaluation of the holistic self development modules: a study among arts and design students / Rohana Hamzah - Hamzah, Rohana (2009)
The Faculty of Art and Design (FSSR), UiTM Shah Alam was formed based on its holistic education mission. However, the main problem occurred especially in developing spiritual domain among arts and design students. Therefore, the purpose of this study is to offer an alternative approach as a complementary to conventional practice in teaching and learning of art and design education by developing, integrating and evaluating holistic self-development modules for spiritual domain based on Islamic philosophy. Therefore, the formula for self-development process which is to render the self-narrowness forces to be under the control of the self-enlightening forces has been developed and tested in this study. Two types of teaching and learning modules have also been developed to present the self development process namely the traditional approach module and the interactive multimedia approach module. In order to measure the effectiveness of these modules on students' self-development from spiritual domain, 'the self-development from spiritual and emotion stability instrument' has been developed. In addition, the students' achievement on product design (as evaluated by educator) and their responsibilities as God's khalifah (the instrument has been developed by researcher) was measured to evaluate the effectiveness of the modules. The exploratory mixed methods research design has been applied during the first stage of research process which enables the researcher to diagnose the teaching and learning problems followed by the quantitative research method of true experimental pretest-posttest design. Students in semester three have been chosen as the respondents because the actual design process only begins during this semester of their study program at FSSR. The findings show that there is a significant difference in self-development level between the experimental groups of students.